Modeling of transient power distribution in a fused fiber coupler - Hairul Shah Aziz, 1979-; Jalil Ali, supervisor; Rosly Ab. Rahman, supervisor; Saktioto, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010